Determinants for perinatal adverse outcomes among pregnant women with preterm premature rupture of membrane: A prospective cohort study - Abebe, Tariku Abewa; Nima, Dawit Desalegn; Mariye, Yitbarek Fantahun; Leminie, Abebaye Aragaw (Frontiers in Reproductive Health, 2022)
Background One of the most critical functions of the fetal membranes is to remain intact until the onset of labor to maintain the protective intrauterine fluid environment. In most pregnancies, spontaneous rupture usually occurs near the end of the first stage of labor. Preterm premature membrane rupture (PROM) occurs when the fetal membrane ruptures before 37 weeks of pregnancy, and it contributes to adverse maternal, fetal, and neonatal outcomes. Therefore, this study aimed to determine the association of determinant factors with adverse perinatal outcomes. Methods A prospective cohort study was conducted on pregnant women with preterm premature membrane rupture (n = 160) attending the teaching hospitals at Addis Ababa University. Socio-demographic and obstetric risk factors with adverse perinatal outcomes include the 5th minute Apgar score, neonatal intensive care unit (NICU) admission, early-onset neonatal sepsis (EONS), respiratory distress syndrome (RDS), perinatal mortality, Chorioamnionitis, and placental abruption were assessed. SPSS version 24, t-test, χ2 test, and logistic regression analysis were used. P-values <0.25 in the bivariate and p < 0.05 in the multiple logistic regression were considered statistically significant. Results The preterm (PROM) rate was 2.2% with perinatal mortality rate of 206/1,000. Gestational age (GA) at delivery was the determinate for low Apgar score at the 5th minute (AOR: 7.23; 95% CI, 1.10, 47.6; p = 0.04). Unable to use steroid (AOR: 8.23; 95% CI, 1.83, 37.0; p = 0.000), GA at membrane rupture (AOR: 4.61; 95% CI, 1.98, 31.8; p = 0.000) and delivery (AOR: 4.32; 95% CI, 1.99, 30.9; p = 0.000) were determinates for NICU admission. EONS was significantly affected by GA at membrane rupture (AOR: 5.9; 95% CI, 1.01, 37.0; p = 0.04). Placental abruption was significantly affected by GA at delivery (AOR: 7.52; 95% CI, 1.15, 48.96; p = 0.04). Conclusion GA at membrane rupture and delivery was the most critical predictors of adverse perinatal outcomes. Local guidelines on the approach and preterm PROM outcome management need to be prepared.